Redes ilegais: o contrabando de agrotóxicos na fronteira Paraná (Brasil)-Paraguai - Horii, Angélica Karina Dillenburg (2014)
The dissertation search to map the smuggling of pesticides in the Paraná (Brazil)-Paraguay border, making use of scientific research, official institutional bodies, journalistic sources, and local, regional, state and national between the years of 2010 to 2012, as a means to collect relevant data and thematic information. The research of work observes the problems existing in the border area with the proliferation of illegal networks, because they have promoted new relationships in the global space, with the promotion of new territories and territorialities. The Paraná (Brazil)-Paraguay border have in your cutout space-temporal subjectivity inherent in those areas, endowed with complexities and cross-border relations between territories, which are important in the discussion of the current geographical knowledge. The indiscriminate use of pesticides on crops in Brazil, placing it to the level of world's biggest consumer, encourages research and promote research directed social, economic and environmental complications, because these goods has created a new paradox in current society, by placing into question the current state of global capitalism